PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) PADA MATERI TRIGONOMETRI DI SMA NAHDLATUL ULAMA 2 GRESIK TAHUN PELAJARAN 2009-2010 - admin admin; Sarwo Edy; DWI IKE KURNIAWATI (Universitas Muhammadiyah Gresik, 2012)
Mathematics is one of lesson has important character, that is caused mathematics is one of lesson in Ujian Nasional (UN). Study activity need mobile character from teacher and student to study aim can reached on the other hand need to created a condition learn fun, so student has interest with study process of mathematics. One of way to study mathematics by using Cooperative Learning of Student Teams Achievement (STAD) type. Subject of this research is student in X-A class with total member 33 of stundent in Senior Hight School Nahdlatul Ulama 2 of Gresik. The purpose of this research is describes study process and teacher response in Cooperative Learning type STAD. This research is quantitative descriptive use One Short Case Study. Data colecthing method in this research by observation, interview and test. This researcher as a observer and helped by two another observers. The research instrument is paper of observation, paper of interview and paper of test. From analysis of data can be conclude that: (1) teacher and student in Senior Hight School Nahdlatul Ulama 2 of Gresik specialy X-A class has enough ability in proces to do Cooperative Learning type STAD at trigonometri matter. (2) teacher in Senior Hight School Nahdlatul Ulama 2 of Gresik specialy X-A class has good response in Cooperative Learning type STAD at trigonometri matter